Compressive Strength of Volcanic Ash/Ordinary Portland Cement Laterized Concrete - Olawuyi B.J.; Olusola K. O. (Civil Engineering Dimension, 2010)
This study investigates the effect of partial replacement of cement with volcanic ash (VA) on the compressive strength of laterized concrete. A total of 192 cubes of 150mm dimensions were cast and cured in water for 7, 14, 21, and 28 days of hydration with cement replacement by VA and sand replacement by laterite both ranging from 0 to 30% respectively, while a control mix of 28-day target strength of 25 N/mm2 was adopted. The results show that the density and compressive strength of concrete decreased with increase in volcanic ash content. The 28-day, density dropped from 2390 kg/m3 to 2285 kg/m3 (i.e. 4.4% loss) and the compressive strength from 25.08 N/mm2 to 17.98 N/mm2 (i.e. 28% loss) for 0-30% variation of VA content with no laterite introduced. The compressive strength also decreased with increase in laterite content; the strength of the laterized concrete however increases as the curing age progresses.